Application of the stabilization effect of a silyl group in radical-polar crossover reactions enabled by photoredox-neutral catalysis. Issue 19 (29th July 2021) - Yang, Naiyuan; Fang, Yewen; Xu, Fenfen; Zhou, Rong; Jin, Xiaoping; Zhang, Li; Shi, Jianxun; Fang, Jianghua; Wu, Hao; Zhang, Zongyong
Abstract : Taking advantage of the stabilization effect of a silyl group, with a bulky but positive nature, a range of less investigated organosilanes could be generally accessed via photoredox-catalysed radical-polar crossover reactions. Abstract : Taking advantage of the stabilization effect of a silyl group, a range of less investigated organosilanes could be generally accessed by means of photoredox-neutral catalysis. With halomethyl silicates as the methylene source, silylcyclopropanes and (cyclopropylmethyl)trimethylsilanes could be prepared via radical addition/3- exo-tet cyclisation cascade reactions. Moreover, using alkyl silicates or 4-alkyl-1, 4-dihydropyridines as the alkyl radical precursors, Giese-type reactions of α-silyl styrenes have also been reported for the formation of 1-aryl-1-(trimethylsilyl)alkanes. These general protocols based on a reductive radical-polar crossover process feature base-, additive-, and exogenous reductant-free conditions.